Characterization of Calcium Silicate Hydrate Gels with Different Calcium to Silica Ratios and Polymer Modifications - Amirhossein Madadi; Jianqiang Wei (Gels, 2022)
Calcium silicate hydrate (CSH) gels, the main binding phases of hydrated cement, are the most widely utilized synthetic materials. To understand the influences of composition and polymers on the reaction kinetics and phase formation, CSH gels with varying Ca/Si ratios and amounts of poly (acrylamide-co-acrylic acid) partial sodium salt (PAAm-co-PAA) were synthesized via a direct method. The CSH gels were characterized through isothermal calorimetry, thermogravimetric analysis (TGA), X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), and Raman spectroscopy at different ages. By increasing the Ca/Si ratio from 0.8 to 1.0, the formation of CSH was enhanced with a 5.4% lower activation energy, whereas the incorporation of PAAm-co-PAA increased the temperature sensitivity of the reactions with an 83.3% higher activation energy. In the presence of PAAm-co-PAA, the reaction rate was retarded at an early age and the negative impact faded over time. The results of an XRD analysis indicated the formation of tobermorite as the main phase of the CSH gels, while the addition of PAAm-co-PAA resulted in a postponed calcium hydroxide consumption and CSH formation, which was confirmed by the decreased FTIR intensity of the C=O bond, Si–O stretching and Si–O bonds. The increased Raman vibrations of Si–O–Si bending Q2, Ca–O bonds, O–Si–O and asymmetric bending vibrations of SiO4 tetrahedra in the presence of PAAm-co-PAA indicate the intercalation of the polymeric phase and internal deformation of CSH gels.